Enrolment purposes, instructional activities, and perceptions of attitudinal learning in a human trafficking MOOC. (1st September 2016) - Watson, Sunnie Lee; Kim, Woori
Abstract: This study examines learner enrolment purposes, perceptions on instructional activities and their relationship to learning gains in a Massive Open Online Course (MOOC) for attitudinal change regarding human trafficking. Using an author-developed survey, learners reported their perceptions on instructional activities and learning gains within the MOOC, as well as their enrolment purposes. Motivations varied with the majority of learners wanting to formulate a viewpoint or to justify their existing viewpoint, with those taking the MOOC in order to earn a formal certification reporting the highest learning gains. Overall, learners perceived lectures and videos as the most impactful instructional strategy. However, learners who reported the personal project activity as the most effective instructional strategy showed the highest learning gain. The authors discuss the instructional design considerations based on these survey results.